2017
DOI: 10.1302/2058-5241.2.160004
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma (PRP) for knee disorders

Abstract: Platelet-rich plasma (PRP) is an autologous blood product with platelet concentrations above baseline values. The process involves the extraction of blood from the patient which is then centrifuged to obtain a concentrated suspension of platelets by plasmapheresis. It then undergoes a two-stage centrifugation process to separate the solid and liquid components of the anticoagulated blood. PRP owes its therapeutic use to the growth factors released by the platelets which are claimed to possess multiple regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 62 publications
2
44
0
2
Order By: Relevance
“…[392,393] Adverse events with PRP treatment were not significantly increased in comparison with other knee OA treatments consistent with earlier studies using PRP as an intervention in knee OA. [393][394][395] HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic [312] [ 313] Hydros, Hydros-TA HMW Triamcinolone acetonide Cortocosteroid [314] Cingal 1900 Triamcinolone acetonide Cortocosteroid [315] Hylan GF-20 HMWCR Triamcinolone acetonide Cortocosteroid [316] HA solution 800 Mannitol Anti-oxidant [317] Go-on matrix Go- Ostenil Plus 1500 Mannitol Anti-oxidant [320] Happyvix 1500 Mannitol Anti-oxidant [320] Happycross 1500 Mannitol Anti-oxidant [320] Synolis V-A 2000 Sorbitol Anti-oxidant [320] HA 4AR conjugate 2200 4 aminoresorcinol Anti-oxidant [321] Ostenil 1000-2000 l-glutathione Anti-oxidant [322] Arthrum HCS 2800 CS GAG [320] Surgical Syonium 2800 CS GAG [320] HA-sCT conjugate 200 Salmon calcitonin DMOAD [323] HA ADAMTS inhibitor n/a ADAMTS inhibitor DMOAD [324] HA hydrogel 60-120 Doxycycline DMOAD [296] Hanox [325] n/a, not available; HMW, high molecular weight; HMWCR, high molecular weight cross-linked.…”
Section: Therapeutic Properties Of Platelet Rich Plasmasupporting
confidence: 81%
See 1 more Smart Citation
“…[392,393] Adverse events with PRP treatment were not significantly increased in comparison with other knee OA treatments consistent with earlier studies using PRP as an intervention in knee OA. [393][394][395] HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic [312] [ 313] Hydros, Hydros-TA HMW Triamcinolone acetonide Cortocosteroid [314] Cingal 1900 Triamcinolone acetonide Cortocosteroid [315] Hylan GF-20 HMWCR Triamcinolone acetonide Cortocosteroid [316] HA solution 800 Mannitol Anti-oxidant [317] Go-on matrix Go- Ostenil Plus 1500 Mannitol Anti-oxidant [320] Happyvix 1500 Mannitol Anti-oxidant [320] Happycross 1500 Mannitol Anti-oxidant [320] Synolis V-A 2000 Sorbitol Anti-oxidant [320] HA 4AR conjugate 2200 4 aminoresorcinol Anti-oxidant [321] Ostenil 1000-2000 l-glutathione Anti-oxidant [322] Arthrum HCS 2800 CS GAG [320] Surgical Syonium 2800 CS GAG [320] HA-sCT conjugate 200 Salmon calcitonin DMOAD [323] HA ADAMTS inhibitor n/a ADAMTS inhibitor DMOAD [324] HA hydrogel 60-120 Doxycycline DMOAD [296] Hanox [325] n/a, not available; HMW, high molecular weight; HMWCR, high molecular weight cross-linked.…”
Section: Therapeutic Properties Of Platelet Rich Plasmasupporting
confidence: 81%
“…[391] A systematic review, which included data from six randomized controlled trials comparing the effectiveness of PRP with other intra-articular injections, exercise, or analgesia for a minimum of 6 months PRP produced statistically significant improvements in WOMAC scores for up to 12 months. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic [312] [ 313] Hydros, Hydros-TA HMW Triamcinolone acetonide Cortocosteroid [314] Cingal 1900 Triamcinolone acetonide Cortocosteroid [315] Hylan GF-20 HMWCR Triamcinolone acetonide Cortocosteroid [316] HA solution 800 Mannitol Anti-oxidant [317] Go-on matrix Ostenil Plus 1500 Mannitol Anti-oxidant [320] Happyvix 1500 Mannitol Anti-oxidant [320] Happycross 1500 Mannitol Anti-oxidant [320] Synolis V-A 2000 Sorbitol Anti-oxidant [320] HA 4AR conjugate 2200 4 aminoresorcinol Anti-oxidant [321] Ostenil 1000-2000 l-glutathione Anti-oxidant [322] Arthrum HCS 2800 CS GAG [320] Surgical Syonium 2800 CS GAG [320] HA-sCT conjugate 200 Salmon calcitonin DMOAD [323] HA ADAMTS inhibitor n/a ADAMTS inhibitor DMOAD [324] HA hydrogel 60-120 Doxycycline DMOAD [296] Hanox Hanox M-XL 1500 n/a Cortivazol Triamcinolone hexacetonide Mannitol + lidocaine clorhydrate Cortocosteroid Cortocosteroid Anti-oxidant + local anaesthetic [325] n/a, not available; HMW, high molecular weight; HMWCR, high molecular weight cross-linked. [393][394][395] www.advancedsciencenews.com www.advtherap.com HA hydrogel n/a Dexamethasone Cortocosteroid [310] Adant (Suprahyal) 500-1000 Tenoxicam NSAID [311] Variofill (Adoderm, Langenfeld, Gmbh) HMWCR Diclofenac Sodium clodronate Triamcinolone acetonide Ropivacaine HCl NSAID DMOAD Cortocosteroid Anaesthetic …”
Section: Therapeutic Properties Of Platelet Rich Plasmamentioning
confidence: 99%
“…Aiming to stop and revert the degeneration associated with OA, IA injections of autologous conditioned serum (ACS), platelet rich plasma (PRP), and mesenchymal stem cell (MSC) have been tested. 9 , 11 , 62 , 63 Their mechanisms of action is reduction of inflammatory reactions mediated by cytokines, and the induction of anabolism and chondrocyte differentiation via growth factors and stem cells contained in it. These methods are promising and some studies have reported them to be safe, well tolerated and, in some cases, superior to IA placebo and HA in terms of pain relief and knee function.…”
Section: Introductionmentioning
confidence: 99%
“…Además de las proteínas mencionadas, se usan otros productos biológicos no recombinantes; entre ellos, el ácido hialurónico y el plasma rico en plaquetas (PRP). Aunque parece ser mejor que la viscosuplementación intraarticular con ácido hialurónico (Paterson et al, 2016), la aplicación de PRP genera controversia debido a los resultados clínicos contradictorios y el beneficio sintomático transitorio reportado después de su aplicación (Shahid & Kundra, 2017). En estudio fase III se encuentra Ampion (albúmina sérica humana < 5kDa), producto biológico no recombinante para aplicación intraarticular que inhibe la secreción de citoquinas proinflamatorias sintetizadas por los linfocitos T (Bar-Or et al, 2014).…”
Section: Tratamientos De Las Lesiones Del Cartílago De La Rodillaunclassified